Tau protein expression and the development of stable microtubules during neuronal differentiation of D310 cells. - Sun, Lijuan. (University of Ottawa (Canada), 1994)
The D310 EC cell line is multipotent and differentiation can be directed along the neuronal pathway by addition of retinoic acid (RA). The correlation between the expression of tau protein and the development of stable microtubule arrays during neuronal differentiation was studied by indirect immunofluorescence, ELISA immunoblotting and Immunogold labelling techniques. By immunofluorescence staining tau protein is not detected in undifferentiated EC cells, but it starts to be expressed at day 3 of RA induction and shows a beaded morphological appearance. The expression of tau increases steadily during neuronal differentiation. Double immunofluorescence labelling demonstrates that the expression of tau protein correlates well with the development of colchicine-resistant microtubules. The levels of total cellular tubulin, total class III $\beta$-tubulin and total tau protein were measured by ELISA. The amount of class III $\beta$-tubulin and tau protein were expressed as a ratio of the relative amount of class III $\beta$-tubulin or tau protein/mg total tubulin. ELISA results support the observations of immunofluorescence staining. The relative amount of tau protein expressed after RA induction increases steadily and parallels the increased expression of class III $\beta$-tubulin, an indicator of neuronal differentiation. Immunoblotting shows that both juvenile and mature isoforms of tau protein are present in RA-induced EC cells. Two isoforms are detected in day 3 RA-induced cells and four isoforms are detected in day 6 RA cells. All four isoforms associate with colchicine-stable microtubules. A beaded morphological distribution of tau along neurite processes seen by immunofluorescence staining suggests that tau protein associates with some, but not all microtubules in neurite processes. The prediction that tau associates with colchicine-resistant microtubules was tested by immunogold labelling at the light and electron microscopic levels.
Keywords: Biology, Molecular.